Benzodithiophene‐Based Spacers for Layered and Quasi‐Layered Lead Halide Perovskite Solar Cells. Issue 14 (21st June 2021) - Primera Darwich, Barbara; Guijarro, Nestor; Cho, Han‐Hee; Yao, Liang; Monnier, Luc; Schouwink, Pascal; Mensi, Mounir; Yum, Jun‐Ho; Sivula, Kevin
Abstract: Incorporating extended pi‐conjugated organic cations in layered lead halide perovskites is a recent trend promising to merge the fields of organic semiconductors and lead halide perovskites. Herein, we integrate benzodithiophene (BDT) into Ruddlesden–Popper (RP) layered and quasi‐layered lead iodide thin films (with methylammonium, MA) of the form (BDT)2 MA n −1 Pb n I3 n +1 . The importance of tuning the ligand chemical structure is shown as an alkyl chain length of at least six carbon atoms is required to form a photoactive RP ( n =1) phase. With N =20 or 100, as prepared in the precursor solution following the formula (BDT)2 MA N −1 Pb N I3 N +1, the performance and stability of devices surpassed those with phenylethylammonium (PEA). For N =100, the BDT cation gave a power conversion efficiency of up to 14.7 % vs. 13.7 % with PEA. Transient photocurrent, UV photoelectron spectroscopy, and Fourier transform infrared spectroscopy point to improved charge transport in the device active layer and additional electronic states close to the valence band, suggesting the formation of a Lewis adduct between the BDT and surface iodide vacancies. Abstract : Siding with another : Side‐chain‐engineered benzodithiopheneammonium (BDT) molecules are shown to be excellent ligands for layered halide perovskites. Tailoring the side chain was found to be crucial in order to obtain crystalline structures whereas the highly conjugated BDT core and its sulfur‐containing moieties afford enhanced photovoltaic charge collection, conversion efficiency, and stability when juxtaposed with conventional phenylethylammonium‐based layered perovskites.